Organização do serviço de saúde e cuidado ao idoso indígena: sinergias e singularidades do contexto profissional - Rissardo, Leidyani Karina; Carreira, Lígia (Revista da Escola de Enfermagem da USP, 2014)
This study aimed to describe the effects of the organization of primary healthcare on the assistance provided to the elderly Kaingang population, according to the perception of health professionals that work in this area. It is a qualitative and descriptive study, supported by ethnography methodological references, and was conducted with ten healthcare professionals that work in Faxinal, an indigenous territory in the state of Paraná, in Brazil. Data was collected from November 2010 to February 2012 through participant observation and interviews. The results revealed that health professionals strive to meet the health needs of the elderly Kaingang people; however, there are negative effects that hinder the professional care, especially limited human resources, lack of training and material resources, heavy workload and high turnover rates. This study highlights the need to improve work conditions in order to provide better healthcare.